MODERN APPROACHES TO THE IMPLEMENTATION OF FORMATIVE ASSESSMENT IN MATHEMATICS LESSONS - Mykhailenko, Liubov (Physical and Mathematical Education, 2022)
Formulation of the problem. Formative assessment plays an important role in modern education. Research shows that the use of formative assessment in the classroom can help improve student performance. The implementation of formative assessment in mathematics lessons requires a balanced understanding of the existing and development of new methodological principles for the organization of formative assessment. Materials and methods. Analysis, generalization, systematization, and classification in the study of scientific and methodical literature with the aim of clarifying the state of development of the researched problem and analyzing different approaches to the implementation of formative assessment in mathematics lessons. Results. In most economically developed countries, at the state level, many efforts have been made to reform the evaluation system, in particular, to introduce formative evaluation of students’ educational achievements. However, not all teachers in these countries practice formative assessment. The main directions of increasing the effectiveness of the implementation of formative assessment include: ensuring the professional development of teachers; creating resources to support formative assessment practices. The following are relevant: selection of techniques and means for formative assessment; peculiarities of using various technologies of formative assessment, for example, providing feedback, holding a conversation in the classroom, organizing student self-assessment; development of assessment tools for various forms of education (online, blended learning); practices in teacher education and professional development that address issues of assessment for mathematics learning and teaching. Conclusions. For several decades, in many countries of the world, joint activities of school administration, teachers, and scientists have been encouraged and supported to introduce formative assessment into the educational process: the role of the teacher and students in formative assessment lessons is clarified; conditions are created for expanding the knowledge and skills of teachers to use specific technologies, techniques, and means of formative assessment; opportunities for combining and using the prospective experience of formative assessment, which can be implemented for teaching mathematics, are studied.